Cost-Effectiveness of the Transmural Trauma Care Model (TTCM) for the Rehabilitation of Trauma Patients. (24th July 2019) - Wiertsema, Suzanne H; van Dongen, Johanna M; Geleijn, Edwin; Huijsmans, Rosalie J; Bloemers, Frank W; de Groot, Vincent; Ostelo, Raymond WJG
Abstract: Objectives: To assess the societal cost-effectiveness of the Transmural Trauma Care Model (TTCM), a multidisciplinary transmural rehabilitation model for trauma patients, compared with regular care. Methods: The economic evaluation was performed alongside a before-and-after study, with a convenience control group measured only afterward, and a 9-month follow-up. Control group patients received regular care and were measured before implementation of the TTCM. Intervention group patients received the TTCM and were measured after its implementation. The primary outcome was generic health-related quality of life (HR-QOL). Secondary outcomes included disease-specific HR-QOL, pain, functional status, and perceived recovery. Results: Eighty-three trauma patients were included in the intervention group and fifty-seven in the control group. Total societal costs were lower in the intervention group than in the control group, but not statistically significantly so (EUR-267; 95 percent confidence interval [CI], EUR-4, 175–3011). At 9 months, there was no statistically significant between-group differences in generic HR-QOL (0.05;95 percent CI, −0.02–0.12) and perceived recovery (0.09;95 percent CI, −0.09–0.28). However, mean between-group differences were statistically significantly in favor of the intervention group for disease-specific HR-QOL (−8.2;95 percent CI, −15.0–−1.4), pain (−0.84;95CI, −1.42–−0.26), and functional status (−20.1;95 percent CI, −29.6–−10.7). Cost-effectiveness acceptability curves indicated that if decision makers are not willing to pay anything per unit of effect gained, the TTCM has a 0.54–0.58 probability of being cost-effective compared with regular care. For all outcomes, this probability increased with increasing values of willingness-to-pay. Conclusions: The TTCM may be cost-effective compared with regular care, depending on the decision-makers willingness to pay and the probability of cost-effectiveness that they perceive as acceptable.